Pendampingan Peningkatan Akuntabilitas Guru Bimbingan dan Konseling di Kota Bogor - Angelina, Putri Ria; Nurihsan, Juntika; Suherman, Uman; Yustiana, Yusi Riksa (GUYUB: Journal of Community Engagement, 2024)
Accountability is a form of responsibility for guidance and counseling teachers in providing guidance and counseling services at schools and for assessing the success rate of the programs that have been implemented. The purpose of this research is preventive and curative efforts to better address issues of accountability among guidance and counseling teachers. The method used in this study is pre-experimental. The experimental group received a treatment in the form of training to improve accountability among guidance and counseling teachers. The measurement tool used is the understanding of accountability as measured by MEASURE, developed by Stone and Dahir, which was administered at the beginning (pretest) and at the end (posttest). The results of this study indicate an increase in the understanding of accountability among guidance and counseling teachers